Structural Biology Meets Biomolecular Networks: The Post-AlphaFold Era - Yan, Wenying; Hu, Guang (Current Bioinformatics, 2022)
Background: Recent progress in protein structure prediction by AlphaFold has opened new avenues to decipher biological functions from the perspective of structural biology based on the proteomics level. Methods: To meet these challenges, in this perspective, three scales of networks for protein structures, including structural protein-protein networks, protein structural networks, and elastic network models were introduced for high-throughput modeling of protein functional sites and protein dynamics. Conclusion: In the post-AlphaFold era, it is assumed that the integration of biomolecular networks may be leveraged in the future to develop a modeling framework that addresses protein structure-based functions with the application in drug discovery.
Keywords: protein dynamics